Analisis Objek Bergerak Dengan Metode Background Subtraction - Akbar iskandar; Irmawaty (Celebes Engineering Journal, 2019)
This study aims to test and analyze the accuracy of the Background Subtraction Method in detecting moving objects in a room with the help of CCTV cameras. Data for this research requires data from various sources such as observations and documentation. The analysis and testing techniques carried out are quantitative and qualitative in order to obtain the expected research results. The results of this study indicate that this application detects movement from within and works by using video samples to detect movements that occur in the room.